3D Content Generation to Moodle Platform to Support Anatomy Teaching and Learning - Baptista, Fabricio Quintanilha [UNESP]; Neto, Mario Popolin; Colombo Dias, Diego Roberto; Guimaraes, Marcelo de Paiva; Ferreira Brega, Jose Remo [UNESP]; IEEE (Ieee, 2016)
Anatomy learning is very important for many courses, and it requires understanding three-dimensional (3D) shapes, most forms of anatomy teaching are offered to students through two-dimensional (2D) resources, such as images and videos. Many software solutions were developed with the purpose of assisting anatomy teaching and learning, arranging varied techniques and assets, as interaction and visualization of 3D virtual models. Despite great features, these solutions lack standards utilization and pedagogical methodology. This paper aims to present a 3D content generation technique to Moodle, one of the most popular platforms for teaching and learning management, built upon a specific pedagogical methodology, and validated by educational experts. The standard used in this technique allow sharing and reuse of content not only among Moodle systems, which are used by a large number of educational institutions and professors but also in other Virtual Learning Environments.